Numerical Solution of Energy Transmission Lines Equivalent Circuit Equations with Adomian Decomposition Method - Serteller, N.F.O.; Ustundag, D. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, analysis for a mathematical model of an equivalent circuit to provide solutions of electrical energy power transmission lines (ETL) with Adomian Decomposition Method (ADM) has been proposed. By using Mathematica program, partial differential equations as a function of voltage (current) forming the model are solved and compared with the finite difference method (FDM). The results of some special examples obtained from ADM and FDM illustrate very good synchronism and show the simplicity and the efficiency of the method.